Gender Differences in the Use of Foul Language in Punjabi - Khushnood Akhter (European Scientific Journal, ESJ, 2023)
This study explores the use of foul language and its types in Punjabi from the perspective of gender. In this context, a corpus of Punjabi foul terminology was gathered from 58 male and female Punjabi speakers from urban and rural areas, through an open-ended questionnaire. The theoretical framework of Battistela (2005) was applied. The data was analyzed in tables through a statistical approach with its frequency and phonetic transcription. The study revealed that, Punjabi speaking people use foul language in many ways, types and situations. The study also found that males use more abusive terminology while there is less use of coarse words by females. The study revealed swear-word use is more derogatory and directed more towards the females rather than the males. Findings from this study contribute to the research on the use of foul language which is still in its infancy and to the lexicology of Punjabi language.